Three-dimensional pedestrian dead reckoning method based on gait recognition. (2018) - Huang, Min; Li, Hua-Zhao; Wu, Xia
With the widespread use of sensors on smartphones, it is becoming easier to use pedestrian dead reckoning (PDR) with smartphones, and making it possible to rely on smartphones for accurate indoor positioning. The existing PDR model is based on two-dimensional effective modelling method of the indoor space, said lack of three-dimensional space. In this paper, the concept of step height is introduced in a creative way, and a three-dimensional PDR model based on gait recognition is proposed, which makes it possible to locate indoor three-dimensional space. The three-dimensional PDR model uses an improved method of step detection and the average accuracy of the model is higher than the traditional 2D PDR model. Meanwhile, the experiment also proved the effectiveness and practicality of the three-dimensional model of the PDR.